2018
DOI: 10.1055/s-0038-1632388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additional Treatments Combined with Conventional Therapies in Pregnant Patients with High-Risk Antiphospholipid Syndrome: A Multicentre Study

Abstract: The effect of additional treatments combined with conventional therapy on pregnancy outcomes was examined in high-risk primary antiphospholipid syndrome (PAPS) patients to identify the most effective treatment strategy. The study's inclusion criteria were (1) positivity to lupus anticoagulant alone or associated with anticardiolipin and/or anti-β2 glycoprotein I antibodies; (2) a history of severe maternal-foetal complications (Group I) or a history of one or more pregnancies refractory to conventional therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…In severe cases with recurrent late pregnancy morbidities, despite treatment with LDA and LMWH, low-dose steroids (10 mg prednisolone) and hydroxychloroquine may be added. 86 In severe treatment-resistant cases, intravenous gamma globulin or repeated plasma exchange/apheresis could, based on small case series with favourable outcomes, be considered. 87 …”
Section: Management Of Oapsmentioning
confidence: 99%
“…In severe cases with recurrent late pregnancy morbidities, despite treatment with LDA and LMWH, low-dose steroids (10 mg prednisolone) and hydroxychloroquine may be added. 86 In severe treatment-resistant cases, intravenous gamma globulin or repeated plasma exchange/apheresis could, based on small case series with favourable outcomes, be considered. 87 …”
Section: Management Of Oapsmentioning
confidence: 99%
“…This study did not separate women who had APS only from those with APS and SLE, and therefore the prevalence of SLE was not uniform across the two groups. However a study isolating subjects with APS (without SLE) and a history of previous pregnancy complications resulted in similar findings of a higher live birth rate and fewer severe pregnancy complications in those treated with HCQ [36]. In a third retrospective study, Mekinian et al showed that women with obstetric APS and refractory obstetric APS treated with HCQ had better pregnancy outcomes, i.e., fewer miscarriages, compared to those without HCQ [37].…”
Section: Hcq In Recurrent Early Miscarriage and '2 Nd And 3 Rd Trimesmentioning
confidence: 84%
“…The addition of HCQ, a drug possibly capable of restoring some of the damage exerted by aPL on trophoblasts in mice models [ 40 , 41 ], has been regarded as the next step in obstetrical APS treatment [ 42 ]. This drug has been reported to be safe in pregnancy and in women with obstetric APS pregnancies, with no [ 43 , 44 ] or minor side-effects [ 45 ], probably due to a limited duration of treatment [ 46 ]. However, we decided to be cautious and only prescribe HCQ to patients with a previously unsuccessful treatment regimen with LMWH and ASA.…”
Section: Discussionmentioning
confidence: 99%